2021
DOI: 10.1155/2021/7363449
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Estimation for the Remained Stress-Strength Model under the Generalized Exponential Lifetime Distribution

Abstract: A stress-strength reliability model compares the strength and stresses on a certain system; it is used not only primarily in reliability engineering and quality control but also in economics, psychology, and medicine. In this paper, a novel extension of stress-strength models is presented. The mew model is applied under the generalized exponential distribution. The maximum likelihood estimator, asymptotic distribution, and Bayesian estimation are obtained. A comprehensive simulation study along with real data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…(Refer Saber and Khorshidian(2021) ). Motivated by this, Saber and Khorshidian [10] introduced the conditional stress -strength reliability R |a,b . Later researchers such as Raid et al [11], and Sabre et al [12] have attempted to estimate reliability under a conditional stress-strength setup in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Refer Saber and Khorshidian(2021) ). Motivated by this, Saber and Khorshidian [10] introduced the conditional stress -strength reliability R |a,b . Later researchers such as Raid et al [11], and Sabre et al [12] have attempted to estimate reliability under a conditional stress-strength setup in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by this, Saber and Khorshidian [10] introduced the conditional stress -strength reliability R |a,b . Later researchers such as Raid et al [11], and Sabre et al [12] have attempted to estimate reliability under a conditional stress-strength setup in recent years. They evaluated the system's reliability in a conditional stress-strength setup where the stress-strength variable follows Kumaraswamy, and Generalised exponential lifetime distributions.…”
Section: Introductionmentioning
confidence: 99%
“…However, our discussion in this article will center around the practical applications and implications of the Poisson Topp-Leone Burr XII (PTL-BXII) model. For more Burr XII extensions see Paranaíba et al [43], Paranaíba et al [42], Yousof et al [58], Korkmaz et al [32], Yousof et al [61], Gad et al [25], Cordeiro [19] and Elsayed and Yousof [24]. Some other useful Burr XII extensions can found in Nasir et al [39], Yousof et al [61], Nasir et al [40], Abouelmagd et al [2] and Abouelmagd et al [3].…”
Section: Introductionmentioning
confidence: 99%
“…A stress-strength reliability model compares the strength and stresses on a certain system; it is used primarily not only in reliability engineering and quality control but also in economics, psychology, and medicine [18]. In the area of stress-strength models, there has been a large amount of work regarding estimation of the reliability parameter, R � p(Y < X), where X and Y are independent random variables and have the same univariate distribution.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Khames and Mokhlis [19] introduced a bivariate general exponential model for the stress-strength reliability model. Saber et al [18] suggested a remained stress-strength model for the generalized exponential model. Jafari and Bafekri [20] made inferences using the stress-strength model for two parameters exponential distribution under the assumption of order statistics.…”
Section: Introductionmentioning
confidence: 99%